High School Students and Cultural Capital from the Perspective of Teachers (Global Journal of Human-Social Science, 2024)
The present research aims to investigate how the high school, from the perspective of the teachers, has been contributing to the cultural formation of its students. This is a qualitative study with a descriptive-analytical approach, which used questionnaires and interviews as data collection procedures. With the data generated from the research, we were able to trace the profile of the participants and learn how teachers develop practices favorable to the expansion of cultural capital. With the analysis of the data, we found some obstacles that teachers face when they intend to develop practices that promote cultural development. They are: structural difficulties, little pedagogical support from the management team, lack of time for the organization of pedagogical work and lack of interest from the students themselves. In addition, the study pointed out that teachers have little experience with cultural actions.
Keywords: cultural capital middle school public school